2010
DOI: 10.2165/11319330-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Varying Degrees of Renal Impairment on the Pharmacokinetics of Duloxetine

Abstract: Dose adjustments for duloxetine are not necessary for patients with mild or moderate renal impairment (CL(CR) > or =30 mL/min). For patients with ESRD or severe renal impairment (CL(CR) <30 mL/min), exposures of duloxetine and its metabolites are expected to increase; therefore, duloxetine is not generally recommended for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 27 publications
2
9
0
2
Order By: Relevance
“… 86 A pharmacokinetics study of 12 individuals with ESRD and 12 healthy controls found that the clearance of duloxetine was more than 2 times longer in patients with ESRD compared with controls. 88 The product insert for duloxetine in the United States currently recommends not using this medication when the creatinine clearance is <30 ml/min, due to decreased clearance by the kidneys. 86 However, regulatory agencies outside the United States have suggested that it can be used at lower doses with careful titration.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“… 86 A pharmacokinetics study of 12 individuals with ESRD and 12 healthy controls found that the clearance of duloxetine was more than 2 times longer in patients with ESRD compared with controls. 88 The product insert for duloxetine in the United States currently recommends not using this medication when the creatinine clearance is <30 ml/min, due to decreased clearance by the kidneys. 86 However, regulatory agencies outside the United States have suggested that it can be used at lower doses with careful titration.…”
Section: Treatmentmentioning
confidence: 99%
“… 86 However, regulatory agencies outside the United States have suggested that it can be used at lower doses with careful titration. 88 …”
Section: Treatmentmentioning
confidence: 99%
“…Duloxetine undergoes hepatic metabolism and renal excretion. The parent drug is highly protein bound (95.7%) with a large volume of distribution, and is not well‐dialysed . The C max and AUC of duloxetine and its inactive metabolites were elevated at least twofold in ESRD patients.…”
Section: Neuropathic Painmentioning
confidence: 99%
“…As a whole, all SNRIs are renally cleared and have associated dosing adjustments in CKD; however, it is only recommended that duloxetine should be avoided in patients with creatinine clearance <30 mL/min, primarily due to an ~2-fold higher area under the curve in those with ESRD 22,23. Venlafaxine is primarily metabolized by CYP2D6 into its active metabolite O-desmethyldesvenlafaxine, and to a lesser extent by CYP3A4 24.…”
mentioning
confidence: 99%